Implementasi Adiwiyata dalam Penanaman Karakter Peduli Lingkungan di Sekolah Dasar - Akbarul Fitra; Jerry Rahman Hakim; Ana Nurhasanah (JURNAL PEDAGOGIK PENDIDIKAN DASAR, 2023)
The rise of problems related to environmental issues makes it urgent to inculcate the character of caring for the environment from an early age. Various programs and initiatives have been launched to create a sustainable environment. One program that has attracted much attention to study is the Adiwiyata program. This study aims to describe the implementation of the Adiwiyata program in cultivating the character of caring for the environment at SDN Bayangkari, Serang City. This study used a descriptive qualitative method with data collection through observation, interviews, and questionnaires. Data validity uses triangulation of sources and techniques. The collected data were then analyzed using qualitative techniques, including data collection, data reduction, data presentation, and drawing conclusions. Implementing adiwiyata at SDN Bhayangkari, Serang City is carried out through habituation activities, integration in learning, and extracurricular activities.